Biodegradable biocomposite pots reinforced with mercerized sugarcane bagasse for sustainable agriculture and plastic waste mitigation - Manar E. Elashry; Elsayed G. Khater; Samir A. Ali (Scientific Reports)
Abstract Biodegradable cultivating pots were fabricated using biocomposites reinforced with fillers such as sugarcane bagasse, compost, peat moss, vermiculite, and activated carbon. This study investigates the impact of mercerization pretreatment on the physical and mechanical properties of pots made with palm wax and Lanette wax matrices. Pretreatment improved fiber-matrix adhesion, reducing water absorption (17–11%) and void content (3.4–1.9%), while increasing tensile strength by 4%. Greenhouse experiments demonstrated enhanced growth performance in Anaheim chili pepper plants grown in treated pots, with specific vegetative indices reaching up to 99.75% and yield improvements of up to 26.6 peppers per plant. The findings emphasize the potential of integrating natural fillers and pretreatment techniques to develop sustainable alternatives to traditional plastic pots, contributing to eco-friendly agricultural practices.